Literature Review: Analisis Faktor Penyebab Keterlambatan Pengembalian Rekam Medis di Rumah Sakit - Alfita Dewi; Ilma Nuria Sulrieni; Chamy Rahmatiqa; Fajrilhuda Yuniko (Lembaga Penerbitan Universitas Esa Unggul, 2021)
AbstractThe quality of medical records describes the quality of health services provided. The return of the medical record file starts from the file being in the treatment room until the file is returned to the medical record unit. Incomplete and not immediately filled out medical resumes cause delays in returning medical records. Therefore, the return of the medical record system is quite important in the medical record unit. This study is a literature review, to see the causes of delays in returning medical records at hospitals in Indonesia. Sources of data come from published research literature, with a total of 18 research articles. Data collection was carried out from March to June 2020. The factor causing the delay in returning medical records was the highest due to the input component. From all journals, 100% of the delays in returning medical records were caused by the input component (Man, Money, Materials, Method, Machine) and 33.3% by the process component. Of the input components, 83.3% were caused by Man factors, 77.8% Method factors, 33.3% Materials factors, 27.8% Machine factors, and 5.5% Money factors. Each hospital must have a clear and firm policy in overcoming delays in returning medical records, with clear and firm policies, the causative factors such as Man, Money, Material, Method, Machine can be minimized and the accuracy of returning medical records can be maximized.Keywords: return, incompleteness, medical records, literature, reviewAbstrakMutu rekam medis menggambarkan mutu pelayanan kesehatan yang diselenggarakan. Pengembalian Rekam Medis dimulai dari berkas tersebut berada diruang rawat sampai berkas tersebut kembali ke unit rekam medis. Pengisian resume medis yang tidak lengkap dan tidak segara dilakukan menyebabkan keterlambatan pengembalian rekam medis. Maka dari itu, pengembalian rekam medis sistem yang cukup penting di unit rekam medis. Penelitian ini merupakan literature review, untuk melihat penyebab keterlambatan pengembalian rekam medis di Rumah Sakit di Indonesia. Sumber data berasal dari literatur hasil penelitian yang telah dipublikasikan, dengan jumlah artikel penelitian sebanyak 18 artikel. Pengambilan data dilakukan dari bulan Maret-Juni 2020. Faktor penyebab keterlambatan pengembalian rekam medis tertinggi disebabkan oleh komponen input. Dari semua jurnal sebanyak 100% keterlambatan pengembalian rekam medis disebabkan oleh komponen input (Man, Money, Materials, Methode, Machine) dan sebanyak 33,3% oleh komponen proses. Dari komponen input tersebut, sebanyak 83,3 % disebabkan oleh faktor Man, 77,8% faktor Methode, 33,3% faktor Materials, 27,8% faktor Machine, dan 5,5% faktor Money. Setiap rumah sakit harus memiki kebijakan yang jelas dan tegas dalam mengatasi keterlambatan Pengembalian Rekam Medis, dengan kebijakan yang jelas dan tegas, faktor penyebab seperti Man, Money, Material, Method, Machine dapat di minimalisir dan ketepatan Pengembalian Rekam Medis dapat dilakukan secara maksimal.Keywords: keterlambatan, pengembalian, rekam medis, literature review